The influence of comorbidities on achieving an N‐terminal pro‐b‐type natriuretic peptide target: a secondary analysis of the GUIDE‐IT trial. (16th November 2021) - Ezekowitz, Justin A.; Alemayehu, Wendimagegn; Rathwell, Sarah; Grant, Andrew D.; Fiuzat, Mona; Whellan, David J.; Ahmad, Tariq; Adams, Kirkwood; Piña, Ileana L.; Cooper, Lawton S.; Januzzi, James L.; Leifer, Eric S.; et al.
Abstract: Aims: N‐terminal pro‐b‐type natriuretic peptide (NT‐proBNP) values may be influenced by patient factors beyond the severity of illness, including atrial fibrillation (AF), renal dysfunction, or increased body mass index (BMI). We hypothesized that these factors may influence the achievement of NT‐proBNP targets and clinical outcomes. Methods: A total of 894 patients with heart failure with reduced ejection fraction were enrolled in The Guiding Evidence‐Based Therapy Using Biomarker Intensified Treatment trial. NT‐proBNP was analysed every 3 months. Results: Forty per cent of patients had AF, the median estimated glomerular filtration rate (eGFR) was 59 mL/min/1.73 m 2 [interquartile range (IQR) 43–76], and median BMI was 29 kg/m 2 (IQR 25–34). Patients with AF, eGFR < 60 mL/min/1.73 m 2, or a BMI < 29 kg/m 2 had a higher level of NT‐proBNP at randomization and over all study visits (all P values < 0.001). Over 18 months, the rate of change of NT‐proBNP was less for patients with AF (compared with those without AF, P = 0.037) and patients with an eGFR < 60 mL/min/1.73 m 2 (compared with eGFR > 60 mL/min/1.73 m 2, P < 0.001). The rate of change of NT‐proBNP was similar for patients with a BMI above or below the median value. Using the 90 day NT‐proBNP, patients with AF, lower eGFR, or lower BMI were less likely to achieve the target NT‐proBNP < 1000 pg/mL than patients without AF, higher eGFR, or higher BMI, respectively. None of these differed between the Usual Care or Guided Care arm for AF, eGFR, or BMI ( P interactions all NS). Conclusions: Patients with AF, a lower BMI, or worse renal function are less likely to achieve a lower or target NT‐proBNP. Clinicians should be aware of these factors both when interpreting NT‐proBNP levels and making therapeutic decisions about heart failure therapies.